A study of the inheritance groups of Hunan Flower Drum Opera - Juan Xie; Jinky Jane C Simeon (ResearchGate, 2024)
Hunan Flower Drum Opera, as one of the important representatives of Chinese traditional opera, has a profound historical background and unique artistic charm. With the acceleration of modernization and changes in social and cultural environment, the inheritance and development of Hunan Flower Drum Opera is facing many challenges. As the core force for the protection, inheritance and innovation of Hunan Flower Drum Opera, the current situation and problems faced by the inherited groups deserve in-depth study and exploration. In this paper, we will discuss the current situation of the heritage group, the challenges faced by the heritage group and the development path in the future.